National bean variety trial; second season planting - National Bean Programme (National Bean Programme, 1990)
In the 1st of 2 trials, 12 bean genotypes were planted during the rainy season (March) in Matapwata (Thyolo, Malawi). Highest yielding (kg/ha) genotypes were 25-2 (616.8), A286 (476.3), 8-7 (423.1), 29 x P692 (348.3), and 25-2 x 8-7 (306.6). Seed size, except for CIAT lines A286 and A344, varied between 29.3 and 44.7 g/100 seeds. In the 2nd trial, 7 bean genotypes were evaluated in association with 3 maize var. in 4 bean producing regions of the country. Responses differed depending on the region, but significantly different responses were observed only in Lilongwe. Genotype 8-7 gave the highest yields, followed by 21-5, G218, 12-4, and 6-5. In general, association with local maize gave the lowest yields. Local bean var. as well as var. 12-4, 8-7, and 21-5 had the largest seed size, varying between 43.1 and 22.0 g/100 seeds. In the trial conducted in Rumphi, bean genotypes had the smallest seed size. (CIAT)